Effects of expanders (high shear conditioning) on growth performance in finishing pigs - S L Johnston; S L Traylor; Robert H Hines; S P Sorrell; I H Kim; G A Kennedy; Joe D Hancock; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1996)
Diets that had been processed using standard, long-term, and expander (high shear) conditioning tended to support greater ADG than an unconditioned meal control diet. Pelleting was necessary to maximize efficiency of growth, but only with standard and long-term conditioning. Indeed, the best efficiencies of gain were for pigs fed the expander processed diets, with no additional benefits from pelleting the expanded mash.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Expander; Pellet; Ulcers; Finishing pigs